Body mass index and shortened telomere length in middle-aged female and male RUNNING HEAD: Middle-aged and shortened telomere length (Baghdad Science Journal, 2022)
Obesity is a risk factor associated with age-related disorders that accelerate aging, and it increases the risk of metabolic diseases. Therefore, this study was conducted to investigate the association of leukocyte telomere length (LTL) with the presence of higher body weight in middle-aged females and males. The study subjects comprised 160 (80 control and 80 higher body mass index BMI groups) with ranging ages of 30-50 years included and stratified for BMI. The physio-biochemical analysis was measured using enzymatic determination. Mean telomere length was determined by using the southern blotting technique. The association analysis revealed a significant variance (P < 0.01) in biochemical parameters between higher BMI groups and control including waist, lipid profile, and the level of estradiol, testosterone, follicle-stimulating hormone, and luteinizing hormone. Mean telomere length was shorter in middle-aged males compared to the females of higher BMI groups and control groups for both age groups. LTL was shorter in the overweight and obese patients compared with the control group, and these differences in LTL obese group were shorter compared to the overweight group. In conclusion, shorter telomere length was observed in middle-aged males associated with higher body weight and lipid abnormalities. Lipid/lipoprotein abnormalities can be used as a predictor for the shortened telomere length and the reduction in adiposity indices can improvement the telomere length in both overweight and obese subjects.